IMPROVING THE TENTH GRADERS’ WRITING AND SPEAKING ABILITIES IN RETELLING NARRATIVE STORIES THORUGH STORYBOARD AT MAN 3 PALEMBANG - Setiawan, Heru (JURNAL DIDASCEIN BAHASA, 2017)
ABSTRACT: This study aimed to find out whether or not there was a significant improvement in writing and speaking abilities in narrative stories of the students who were taught by using Storyboard and those who were not. This study applied a quasi experimental design. The population of the study was the tenth graders with the total number of 224, where sixty-four students were taken as the sample by using purposive sampling. The data were collected by using writing and speaking tests and analyzed statistically by using paired-sample ttest and independent sample t-test. Based on the result independent sample t-test for writing test and the value of t-obtained (6.042) was higher than critical value of t-test (2.000 and 1.994). In addition, the value of t-obtained of speaking (4.649) was higher than critical value of t-test (2.000 and 1.994). This means that there was significant improvement in the abilities to write and speak narrative stories between the students who were taught by using Storyboard and those who were not. Thus, the use of storyboard could improve the students‘ writing and speaking abilities in retelling narrative stories. Keywords: Improving, writing, speaking, abilities, and storyboard